Impact on clinical practice of the implementation of guidelines for the toxicity management of targeted therapies in kidney cancer. The protect-2 study. Issue 1 (December 2016) - Lainez, Nuria; García-Donas, Jesús; Esteban, Emilio; Puente, Javier; Sáez, M.; Gallardo, Enrique; Pinto-Marín, Álvaro; Vázquez-Estévez, Sergio; León, Luis; García-Carbonero, Icíar; Suárez-Rodríguez, Cristina; Molins, Carmen; et al.
Abstract Background The impact of such recommendations after their implementation of guidelines has not usually been evaluated. Herein, we assessed the impact and compliance with the Spanish Oncology Genitourinary Group (SOGUG) Guidelines for toxicity management of targeted therapies in metastatic renal cell carcinoma (mRCC) in daily clinical practice. Methods Data on 407 mRCC patients who initiated first-line targeted therapy during the year before and the year after publication and implementation of the SOGUG guideline program were available from 34 Spanish Hospitals. Adherence to SOGUG Guidelines was assessed in every cycle. Results Adverse event (AE) management was consistent with the Guidelines as a whole for 28.7 % out of 966 post-implementation cycles compared with 23.1 % out of 892 pre-implementation cycles (p = 0.006). Analysis of adherence by AE in non-compliant cycles showed significant changes in appropriate management of hypertension (33 % pre-implementation vs. 44.5 % post-implementation cycles;p < 0.0001), diarrhea (74.0 % vs. 80.5 %;p = 0.011) and dyslipemia (25.0 % vs. 44.6 %;p < 0.001). Conclusions Slight but significant improvements in AE management were detected following the implementation of SOGUG recommendations. However, room for improvement in the management of AEs due to targeted agents still remains and could be the focus for further programs in this direction.